HPV infection and bacterial microbiota in the placenta, uterine cervix and oral mucosa - Heidi Tuominen; Samuli Rautava; Stina Syrjänen; Maria Carmen Collado; Jaana Rautava (NATURE PUBLISHING GROUP, 2022)
We investigated the association between HPV infection and bacterial microbiota composition in the placenta, uterine cervix and mouth in thirty-nine women. HPV DNA genotyping of 24 types was conducted using Multimetrix (R). Microbiota composition was characterized by 16S rRNA gene sequencing. HPV DNA was detected in 33% of placenta, 23% cervical and 33% oral samples. HPV16 was the most frequent type in all regions. HPV infection was associated with higher microbiota richness (p = 0.032) in the mouth but did not influence microbial diversity or richness in other samples. HPV infection was associated with higher abundance of Lactobacillaceae (p = 0.0036) and Ureaplasma (LDA score > 4.0, p < 0.05) in the placenta, Haemophilus (p = 0.00058) and Peptostreptococcus (p = 0.0069) genus in the cervix and Selenomonas spp. (p = 0.0032) in the mouth compared to HPV negative samples. These data suggest altered bacterial microbiota composition in HPV positive placenta, cervix and mouth. Whether the changes in bacterial microbiota predispose or result from HPV remains to be determined in future studies.